One-Year Post COVID-19 Change in Physical Fitness of Primary School Children and Its Individual-Level Predictors - Brigita Mieziene; Laurynas Dilys; Arunas Emeljanovas (OVS LLC, 2024)
Objectives. The study aimed to evaluate physical fitness and its dynamics in a year among primary school children aged 7 to 10 years old concerning the child's individual factors (health-related: physical activity, sedentary behaviour; and psychosocial: physical activity enjoyment). Materials and methods. The study involved a sample consisting of 902 1st-3rd grade students (49% of boys and 51% of girls), who participated in physical fitness testing at baseline and follow-up in a year. Additionally, questionnaire-based data were collected from students and parents. Physical fitness was evaluated by administering eight out of nine tests from a 9-item test battery developed by Fjørtoft et al. (2011). The participants' height and weight were measured using a mechanical stadiometer platform (Seca 274, Hamburg, Germany; TEM50.01%) and a portable electronic scale - a TANITA BC 420 SMA (Tanita Europe BV, Amsterdam, The Netherlands), respectively. Physical activity, sedentary behaviour, participation in sports, physical activity enjoyment were evaluated by children and parents at different time points. Results. The results indicated that physical fitness had improved from baseline to follow-up, with some exceptions for particular tests and genders. Vigorous physical activity at Time 1 predicted better hand muscle strength (Std β = .18) and agility (Std β = -.12) at Time 2. The findings showed that participation in sports at Time 1 was also predictive of improved agility (Std β =.15). Moderate to vigorous physical activity at Time 1 predicted enhanced speed at Time 2 (Std β = -.16). The motivation for physical activity at Time 2 was found to be related to improvements in agility (Std β = - 0.18) and speed (Std β = -0.30), while there was a decline in hand muscle strength (Std β = -0.11). Altogether, predictors were able to significantly explain 10 percent of agility and 13 percent of speed test results. Conclusions. As children grow and develop, their physical fitness levels tend to change in response to various factors including different physical activity indicators, as well as motivation for engaging in physical activity.